1998
DOI: 10.1038/sj.onc.1201992
|View full text |Cite
|
Sign up to set email alerts
|

FGF4 dissociates anti-tumorigenic from differentiation signals of retinoic acid in human embryonal carcinomas

Abstract: A subset of male germ cell cancers presenting with advanced stage abundantly express the ®broblast growth factor-4 (FGF4). FGF4 expression is restricted in vitro to undi erentiated embryonal carcinomas (ECs). During induced di erentiation, FGF4 expression is repressed in maturation sensitive but not resistant human ECs, suggesting FGF4 plays an important role in malignant growth or di erentiation of ECs. To explore these FGF4 signals in male germ cell cancers, the multipotent human EC NTERA-2 clone D1 (NT2/D1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
5
25
0
1
Order By: Relevance
“…For example, expression of the growth factors FGF4 and TGFa is downregulated and expression of Wnt-13 is induced following treatment with either RA or HMBA, consistent with the hypothesis that common extracellular signaling pathways are important for multiple NTERA-2 di erentiation programs (Miller et al, 1994;Wakeman et al, 1998). Down-regulation of the growth factors FGF4, TGFa, and TDGF-1 (CRIPTO) has been shown to contribute to the reduced proliferative and tumorigenic potential in di erentiated NTERA-2 cells (Baldassarre et al, 1996(Baldassarre et al, , 1997Baselga et al, 1993;Maerz et al, 1998). In contrast, addition of recombinant bone morphogenetic protein-7 has been shown to induce di erentiation of NTERA-2 cells along a pathway distinct from that induced by RA or HMBA (Andrews et al, 1994).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…For example, expression of the growth factors FGF4 and TGFa is downregulated and expression of Wnt-13 is induced following treatment with either RA or HMBA, consistent with the hypothesis that common extracellular signaling pathways are important for multiple NTERA-2 di erentiation programs (Miller et al, 1994;Wakeman et al, 1998). Down-regulation of the growth factors FGF4, TGFa, and TDGF-1 (CRIPTO) has been shown to contribute to the reduced proliferative and tumorigenic potential in di erentiated NTERA-2 cells (Baldassarre et al, 1996(Baldassarre et al, , 1997Baselga et al, 1993;Maerz et al, 1998). In contrast, addition of recombinant bone morphogenetic protein-7 has been shown to induce di erentiation of NTERA-2 cells along a pathway distinct from that induced by RA or HMBA (Andrews et al, 1994).…”
Section: Introductionsupporting
confidence: 53%
“…To our knowledge, this is the ®rst study examining the e ects of overexpressing a secreted protein that is up-regulated during NTERA-2 di erentiation. Interestingly, the phenotype observed when CREG is overexpressed in these cells is di erent from the e ects of constitutive expression of other proteins implicated in the control of NTERA-2 cell growth and di erentiation (Baselga et al, 1993;Maerz et al, 1998;Moasser et al, 1995;Spinella et al, 1998). We have found that CREG increases the number of cells that di erentiate both in the absence of an inducer and in response to RA.…”
Section: Discussionmentioning
confidence: 54%
“…In order to avoid massive cell death, observed when Sox2 levels were elevated at least 4-fold above the endogenous level (Mitsui et al, 2003;Kopp et al, 2008;Tonge and Andrews, 2010), we generated cell clones with SOX2 expression driven by cytomegalovirus immediate-early promoter (CMV-IE), which exhibited weak activity in ES and EC cells (Niwa et al, 1991;Liew et al, 2007). The use of CMV-driven constitutive overexpression in NT2/D1 cells has been reported for several genes, such as pluripotency-related fibroblast growth factor-4 (FGF-4) and p27, as well as for FLJ11259/DRAM (Maerz et al, 1998;Baldassarre et al, 2000;Kerley-Hamilton et al, 2007). Using this expression system we obtained 54 resistant colonies.…”
Section: Discussionmentioning
confidence: 99%
“…This RA-and di erentiationsensitive enhancer element contains OCT3/4 and Sox2 sites, but does not contain an RARE. The decline of FGF4 mRNA and protein expression re¯ects e ective RA-induced di erentiation and growth suppression of murine teratocarcinomas and human embryonal carcinomas and is`downstream' of direct retinoid receptordriven transactivation in this di erentiation program (Moasser et al, 1994;Yuan et al, 1995;Maerz et al, 1998). E ects of wild-type p53 and DN-p53 overexpression on FGF4 transcription were studied using this reporter assay.…”
Section: Effect Of P53 On a Differentiation State-dependent Fgf4 Repomentioning
confidence: 99%